Book of Job THE FAITHFUL JOB AND HIS JOURNEY TOWARD A DEEP AWARENESS OF WISDOM (JOB 42,1-6) - S.S.L., Paulus Halek Bere (Forum, 2025)
The Book of Job is a profound piece of wisdom literature in the Old Testament, exploring themes of suffering, divine justice, and human righteousness. It is named after its central character, Job, a man described as "blameless and upright" (Job 1:1). Reading the book of Job, the reader will encounter many tensions. The author has presented some actors: God, Satan, Job’s three friends, Job’s family and of course the main character, Job. Every character plays their own role that has the connection with Job. In his faithful journey toward a deep awareness of wisdom, Job come to find the real image of God and his Wisdom for human life. With a restored sense of self and a new way of looking at things, Job become a co-creator and player in the new world of life. Job remains being faithful to God in prologue and epilogue.